Pengaruh Metode Pembelajaran Inkuiri dan Diskusi pada Materi Pokok Bentuk Aljabar terhadap Kemampuan Komunikasi dan Kemampuan Pemecahan Masalah Matematika - Ali Sadikin Wear; Renny Indrawati (Universitas Indraprasta PGRI, 2017)
The research is aimed to know; 1) interaction of inquiry learning method application and discussion on communication ability and student’s mathematics problem solving skills on multivariate. 2) the impacts of learning method on mathematics communication ability on univariat.3) the impacts of learning method on mathematics problem solving skills on univariat. This research is false experiment used non equivalent control group design with 2 factors measurement technique. The instrument is essay test (problem solving and communication question). This research was conducted at public SMP in Palmerah distric, west Jakarta. The sample is the students of class VIII about 140 students. Data analyze used MANOVA analysis. The result of this research is: 1) there are significant impacts of learning method on communication ability and mathematics problem solving skills on multivariate. 2) there are significant impacts of learning method on mathematics communication ability on univariat 3) there isn’t significant impact of learning method on mathematics problem solving skill.